Palaeopathology of aboriginal Australians health and disease across a hunter-gatherer continent - Webb, Stephen; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 1995)
While their health has suffered enormously because of the arrival of the Europeans, it is assumed that Aboriginal people enjoyed good health before 1788. Using data collected from all parts of the continent, this 1995 book studies the health of Australia's original inhabitants over 50,000 years. It represents the first continental survey of its kind and is the first to quantify and describe key aspects of Australian hunter-gatherer health. The book takes a theoretical approach to Upper Pleistocene regional epidemiology and presents empirical data of the health of late Pleistocene and Holocene populations. Major categories of disease described are: stress, osteoarthritis, fractures, congenital deformations, neoplasms and non-specific and treponemal infections. The author also describes surgical techniques used by Aboriginal people. Offering fresh insight into the study of Australian prehistory and Aboriginal culture, this book will be accessible to specialists and general readers alike. It illuminates the origins of human disease, and will fill a gap in our knowledge of health in the Australasian region.
1. Introduction -- 2. Australian palaeopathology, survey methods, samples and ethnohistoric sources -- 3. Upper Pleistocene pathology of Sunda and Sahul: some possibilities -- 4. Pathology in late Pleistocene and early Holocene Australian hominids -- 5. Stress -- 6. Infectious disease -- 7. Osteoarthritis -- 8. Trauma -- 9. Neoplastic disease -- 10. Congenital malformations -- 11. Motupore: the palaeopathology of a prehistoric New Guinea island community -- 12. The old and the new: Australia's changing patterns of health.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Electronic books; Paleopathology -- Australia; Aboriginal Australians -- Health and hygiene